Respuesta :
7(x - 2) = 3(x + 4)
7x - 14 = 3x + 12
7x - 3x = 12 + 14
4x = 26
x = 26/4
x = 6 1/2 (answer is 6 and 1/2)
7x - 14 = 3x + 12
7x - 3x = 12 + 14
4x = 26
x = 26/4
x = 6 1/2 (answer is 6 and 1/2)
Answer: The required solution is x = 6.5.
Step-by-step explanation: We are given to solve the following equation :
[tex]7(x-2)=3(x+4)~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~(i)[/tex]
To solve the given equation, we need to find the value of the unknown variable x.
The solution of equation (i) is as follows :
[tex]7(x-2)=3(x+4)\\\\\Rightarrow 7x-14=3x+12\\\\\Rightarrow 7x-3x=12+14\\\\\Rightarrow 4x=26\\\\\Rightarrow x=\dfrac{26}{4}\\\\\Rightarrow x=6.5.[/tex]
Thus, the required solution is x = 6.5.